Increased Yield and Improved Transplantation Outcome of Mouse Islets with Bovine Serum Albumin. (9th December 2012) - Bertera, Suzanne; Balamurugan, A. N.; Bottino, Rita; He, Jing; Trucco, Massimo
Abstract : Isolation and transplantation of rodent islets are frequently used as a tool for predicting the behavior of new protocols for islet allotransplants in type 1 diabetes patients. Bovine serum albumin (BSA) is recognized as a protease inhibitor possibly protecting function and viability in islets. For this study, the addition of 0.2% BSA to the isolation protocol resulted in a 30% increase in islet yields while other parameters, such as viability and function, retained high islet quality. In vivo, a minimal mass of 70 BSA treated islets showed their ability to control glycemia levels in diabetic mice by bringing the average blood glucose to 153 ± 13.2  mg/dL compared to 288 ± 22.6  mg/dL without BSA. Our results show that the simple addition of BSA to the isolation protocol constitutes a reliable and reproducible method for increasing islet yield. Also adding BSA to the transplantation medium improves islet function in vivo . The method outlined here can reduce the overall number of animals needed per experiment and also reduce the time and resources needed for islet preparation.